Simulasi Penggunaan Komponen Smart Building untuk Meningkatkan IKE di Gedung Rektorat Universitas Udayana - Permana, Adhi; Hartati, Rukmi Sari; Kumara, I Nyoman Satya (Majalah Ilmiah Teknologi Elektro, 2022)
One of the important aspects in energy management is energy audit activities. he benefits of an energy audit include recommendations for actions to be taken to improve energy efficiency, reduce costs and save money on energy bills.  This study aims to obtain information on the efficiency of the use of electrical energy in the rectorate building of Udayana University and how big the potential for saving electrical energy is through testing energy-saving equipment. The results of the measurement, observation and data collection of the load at the Udayana University rectorate, the total power and electrical energy consumption of the Udayana University Rectorate building are 120.12 kW and 15521.02 kWh, respectively. The biggest need for electricity supply is air conditioning, which is 61.5 kW with energy consumption of 62%. In general, the Rectorate building of Udayana University has an IKE value of 49.43 kWh/m2/year. The IKE value for the AC/non-AC building category is 4.12 kWh/m2/month (very efficient). Meanwhile, in terms of IKE per room, there is still a value below the efficient category because electrical equipment is still / left on when working hours are over, especially lights and air conditioners. The application of Smart Building equipment with the aim of efficient use of electrical energy shows a decrease in lighting electrical energy consumption by 161.25 kWh (31%) while for air conditioning by 143.86 kWh (11%).